Pendidikan Inkulturasi Nilai Budaya Keluarga pada Santri Pondok Pesantren Darul Huffadh Kabupaten Bone - Amiruddin Amiruddin; Rifal Rifal (Seminar Nasional LP2M UNM, 2019)
This article discusses the enculturation education of family cultural values in students of Darul Huffadh Islamic Boarding School in Bone Regency. Enculturation is a process that takes place from childhood from a small environment (family) to a large environment (community). This research uses a qualitative method with descriptive type. Data collection techniques were obtained by field research which included observation, documentation and interviews. The data analysis techniques through data reduction, data presentation and drawing conclusions. Facts in the community show that not a few pesantren children are 'damaged' when outside the pesantren or immediately after graduating from pesantren which may be the cause is due to lack of optimal enculturation that he gets in the family. Islamic boarding school students Darul Huffadh began entering boarding schools aged 13 years where the period was still a time of needing education from parents in order to be able to accept family cultures perfectly. However, at that age they are far from potential parents who are unable to accept family culture so that they can eventually deviate. There is a growing striotype in the Kajuara community, that only thugs enter pesantren. It was during the pesantren that they learned ahklak and religious understanding. Where enculturation is associated with transmitting a culture that has been considered good by the family for a long time to be cared for. As happened in the Darul Huffadh Islamic Boarding School, most of the returnees included their families from those who had been students in the place.